DEVELOPING ENGLISH MATERIALS USING ENGLISH-INDONESIAN MIXED SONG LYRICS TO TEACH VOCABULARY - Cahyaningsari, Vinta; Saleh, Mursid (Language Circle: Journal of Language and Literature, 2016)
The fifth graders of Isriati Baiturrahman 2 Elementary School Semarang had problems to study English Vocabulary. They didnâ€™t enjoy to study English vocabulary using drill and writing method done by the teacher. They need the interactive English materials which make them enjoy to study English, especially to improve their vocabulary. This study employed Research and Development design to develop the English materials using English-Indonesia mixed song lyrics to teach Vocabulary. Observation, questionnaire, interview, validation, and pre-test also post test were administered to collect the data. From the results of data collection the writer found that using English-Indonesian mixed song lyrics is effective to teach vocabulary. The average score of pretest was 67,00 and of post-test was 88,38. It means that English-Indonesia mixed song lyrics to teach vocabulary could be implemented in improving the learnersâ€™ vocabulary competence. Therefore, English teachers are suggested to employ the English-Indonesian mixed song lyrics for their future teaching materials.Â